Dead standing pine trees in a boreal forest landscape in the Kalevala National Park, northern Fennoscandia : amount, population characteristics and spatial pattern - Kuuluvainen, Timo; Aakala, Tuomas; Várkonyi, Gergely (Springer Singapore, 2017)
Abstract Background After their death, Scots pine trees can remain standing for decades and sometimes up to 200 years, forming long-lasting and ecologically important structures in boreal forest landscapes. Standing dead pines decay very slowly and with time develop into ‘kelo’ trees, which are characterized by hard wood with silvery-colored appearance. These kelo trees represent an ecologically important, long lasting and visually striking element of the structure of natural pine-dominated forests in boreal Fennoscandia that is nowadays virtually absent from managed forest landscapes. Methods We examined and mapped the amount, structural features, site characteristics and spatial distribution of dead standing pine trees over a ten hectare area in an unmanaged boreal forest landscape in the Kalevala National Park in Russian Viena Karelia. Results The mean basal area of dead standing pine trees in the forested part of the landscape was 1.7 m2∙ha−1 and the estimated volume 12.7 m3∙ha−1. From the total number of standing dead pine trees 65% were kelo trees, with a basal area of 1.1 m2∙ha−1 and volume of 8.0 m3∙ha−1, the remainder consisting of standing dead pines along the continuum between a recently dead tree and a kelo tree. Overall, standing dead pines were distributed throughout the study area, but there was a tendency towards spatial clustering up to <100 m distances. Standing dead pines were most commonly situated on flat ground or in the mid slope in the local topography. In addition, standing dead pines contributed to substrate diversity also by commonly having charred wood and broken tops. Based on the presence of dead pine snags in different stage of transition from a recently dead pine to a kelo with silvery surface, it seems evident that the process of kelo recruitment was continuously in action in the studied landscape. Conclusions Kelo trees are an omnipresent feature in natural pine-dominated forest landscapes with important contribution to forest structural and substrate diversity. Because of ...